2009
DOI: 10.1016/j.canlet.2008.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Prostate stem cell antigen: A prospective therapeutic and diagnostic target

Abstract: The development of novel clinical tools to combat cancer is an intense field of research and recent efforts have been directed at the identification of proteins that may provide diagnostic, prognostic and/or therapeutic applications due to their restricted expression. To date, a number of protein candidates have emerged as potential clinical tools in the treatment of prostate cancer. Discovered over ten year ago, prostate stem cell antigen (PSCA) is a cell surface antigen that belongs to the Ly-6/Thy-1 family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 46 publications
3
64
0
Order By: Relevance
“…10 One potential candidate, overexpressed in both local and metastatic prostate cancer, is prostate stem cell antigen. 11,12 In contrast with other prostate cancer-associated tumor antigens, prostate stem cell antigen has been recognized as a truly prostate-specific membranebound protein, which participates in membrane recycling and becomes internalized by ligand-induced endocytosis. 11 In this study, we engineered a dual-function nanoparticlebased system for in vivo application using an electrostatic and covalent layer-by-layer assembly strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 One potential candidate, overexpressed in both local and metastatic prostate cancer, is prostate stem cell antigen. 11,12 In contrast with other prostate cancer-associated tumor antigens, prostate stem cell antigen has been recognized as a truly prostate-specific membranebound protein, which participates in membrane recycling and becomes internalized by ligand-induced endocytosis. 11 In this study, we engineered a dual-function nanoparticlebased system for in vivo application using an electrostatic and covalent layer-by-layer assembly strategy.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In contrast with other prostate cancer-associated tumor antigens, prostate stem cell antigen has been recognized as a truly prostate-specific membranebound protein, which participates in membrane recycling and becomes internalized by ligand-induced endocytosis. 11 In this study, we engineered a dual-function nanoparticlebased system for in vivo application using an electrostatic and covalent layer-by-layer assembly strategy. 13 Our formulations were characterized by a core-shell structure with a hydrophobic core providing a natural carrier environment for hydrophobic imaging and chemotherapeutic agents, and a multilayer shell endowing the particle with high aqueous dispersity, antibiofouling properties, and stability in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Development of molecular diagnostic methods using novel clinical tools to detect breast cancer at all stages is an area of intense research activity and recent efforts have been directed at the identification of biomarkers that may have diagnostic, prognostic and/or therapeutic 42 applications (Raff et al, 2009). Biomarker research concerned with single nucleotide polymorphisms (SNPs) is expected to open up a new era in the field of cancer research and cancer early diagnostics (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The PSCA gene, encoding a 123 amino acid cell surface protein with 30% homology to stem cell antigen type 2 (SCA-2), an immature lymphocyte cell surface marker (Raff et al, 2009;Yeager et al, 2008), is more highly expressed in human prostate cancer than normal tissues, and also in placenta, so it is an ideal target for cancer diagnosis and therapy (Reiter et al, 1998). Several studies have revealed a correlation between upregulation of PSCA and relevant clinical benchmarks, such as the Gleason score and metastasis in prostate cancer, while others have demonstrated the efficacy of PSCA targeting in treatment through various modalities (Raff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation